The foreign trade of mainland China - Mah, Feng-hwa; Social Science Research Council (Edinburgh : University Press, 1972)
A monograph of the Committee on the Economy of China of the Social Science Research Council
Bibliography: p. [254]-265.
ijb, 15/01/2019
Loans
Keywords: Commerce; China